Are Islamic indices a viable investment avenue? An empirical study of Islamic and conventional indices in India. Issue 3 (10th June 2020) - Alam, Mahfooz; Ansari, Valeed Ahmad
Abstract : Purpose: This study aims to empirically compare the performance of Islamic indices vis-à-vis to their conventional counterparts in India. Design/methodology/approach: The performance of the Islamic and selected conventional indices is evaluated using various risk-adjusted performance measures such as Sharpe ratio, Treynor ratio, M-square (M 2 ) ratio, information ratio, capital asset pricing model (CAPM), Fama-French three-factor model and Carhart four-factor model in India context. The period of study is from December 2006 to 2018. Findings: The risk-adjusted performance measures based on the Sharpe ratio, Treynor ratio, information ratio, the M 2 ratio show that the return of Islamic indices provides slightly superior performance. However, performance investigated using CAPM, Fama-French and Carhart benchmarks produce a statistically insignificant differences in return of the Islamic and conventional benchmarks. Research limitations/implications: The Sharīʿah-compliant indices can provide a viable, ethical and alternative investment avenue for faith-based investors as it will not make them worse off in comparison to the conventional benchmarks. This also offers opportunity to conventional investors for portfolio diversification. The promotion of faith-based investment can serve as a tool for financial inclusion to attract a huge segment of Indian population in the formal financial system. The findings of the study suffer from the limitation of small sample size and empirical methods used. Originality/value: This study contributes to the literature on the comparative performance of Islamic and conventional indices in general and emerging markets, in particular, using most recent data and covering a relatively long span of time. To the best of the knowledge, this is the first comprehensive study examining the performance of Islamic indices, using multiple Islamic indices and various risk-adjusted measures in the Indian context.